Pengembangan Media Pembelajaran Wordwall Berbasis Project Based Learning untuk Meningkatkan Keterampilan Menulis Peserta Didik Kelas IV SDN 113 Seluma - Wityani, Putu; Muktadir, Abdul; Gumono (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this research is to develop, describe the characteristics, logical feasibility, user response and effectiveness of wordwall learning media based on project based learning to improve the description writing skills of grade IV students of 113 Seluma public elementary school. The type of research used is R&D (Rescearch and Development) research with the ADDIE development model. The types of data used are qualitative and quantitative data using instruments in the form of interviews, needs analysis questionnaires, expert validation sheets, and user response questionnaires. The results of the study show that wordwall learning media is able to increase student interaction. Logically, wordwall learning media is feasible to use based on the results of material validation 0.95, linguists 0.83, media/design experts 0.95, which is a high validity category. User responses show a 100% percentage of the attractiveness of wordwall learning media. The effectiveness of wordwall learning media is very high, this is shown by the average N-Gain test of 85.65 or 86% which is included in the effective category. So it can be concluded that the use of wordwall learning media is able to improve the description writing skills of grade IV students of SD Negeri 113 Seluma.